Assessment of Knowledge and awareness of global warming among inhabitants of industrial areas of an urban community in Nigeria (2016)
Global warming with its attendant consequences such as extreme heat, natural disasters, poor air quality and allergens has increased health problems. The risk of injury, illness and resulting death among inhabitants are expected to be frequent and intense especially in areas with heavy industrial presence. The current low level of literacy and the socio-economic situation of Nigerians could be responsible for their low consciousness of this unpreventable changes in our climate in one hand and lack of willingness on the part of people to seek environmental health and safety information on the causes, effect and how to mitigate global warming on the other hand f This study focuses on assessment of knowledge and awareness of causes, effects and mitigating measures of global warming among inhabitants of industrial areas of Ibadan southwestern Nigeria. In this descriptive survey, purposive sampling technique was used to select 200 respondents from among the inhabitants of this area. A questionnaire with reliability co-efficient (r) of 0.78 was used for data collection. Two research questions were answered and three hypotheses tested at 0.05 level of significance. Statistical methods such as Chi-square, frequency count, simple percentage and pie chart were used for data analysis. (Results showed that only 20% had 34.0% had negative attitude while 81 (40.5%) were indifferent, all the three hypotheses were rejected. Consequently, it was deduced that respondents have significant knowledge of global warming. In recommendation, people's environmental health seeking behaviour should be promoted through multidisciplinary and interdisciplinary research and the development of inclusive environmental health and safety intervention strategies.